Hubungan Aspek Sosial Ekonomi dengan Persepsi Petani terhadap Usahatani Karet di Kecamatan Lubai - Siahaan, Yosua Partahian; Harianto, Harianto; Pambudy, Rachmat (AGRICA, 2024)
Many rubber farmers even consider converting their land to other commodities that are considered more profitable or more stable. Farmers' decisions to convert land are often due to problems with economic, technical, and environmental aspects. Rubber farming faces various challenges that cause shifts in farmers' perceptions of the sustainability of this commodity. The objectives of this study were to 1) Analyze farmers' perceptions of rubber farming and 2) Analyze the relationship between socio-economic aspects of farmers' perceptions of rubber farming. This study used 112 rubber farmer respondents, with a population of 543 rubber farmers in the Lubai District. The location was selected purposely based on the same considerations, namely sub-districts, and villages that produced the largest decline in the amount of rubber land area and produced the largest rubber production. Data were collected in a cross-section. Farmers' perceptions of rubber farming based on economic, technical, and environmental aspects are fairly good, with an average score of 2.70. The economic aspect is the most influential aspect on farmers' perceptions of rubber farming activities with an average score of 2.21. The socioeconomic aspect that has a significant relationship to the perception of rubber farming is the level of education with a correlation coefficient value of 0.274913 which indicates a weak level of closeness.